2014
DOI: 10.1016/j.drugalcdep.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Toward a comprehensive developmental model of smoking initiation and nicotine dependence

Abstract: Background This study aims to identify predictors of smoking initiation and nicotine dependence (ND) to develop a comprehensive risk-factor model based on Kendler’s development model for major depression. Methods Data were drawn from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), Wave 2 (n = 34,653). Risk factors were divided into 5 developmental tiers according to Kendler’s model (childhood, early adolescence, late adolescence, adulthood, past-year). Hierarchical logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 83 publications
4
28
1
Order By: Relevance
“…Similar to smoking, current and lifetime nicotine dependence prevalences were higher among adults with past-year AUDs/ SUDs and lifetime AUDs than those without (Table 3). While this was generally consistent across studies, a study using data from adults who reported lifetime smoking and completed Wave 2 of the NESARC found that respondents with a past-year AUD were more likely to report past-year nicotine dependence while adults with lifetime AUD were less likely to report past-year nicotine dependence compared to those without AUDs 40 perhaps due to those with remitted AUDs being more likely to quit smoking (see Table 4). In that study, there were no significant gender differences in the relationships between AUDs/SUDs and past-year nicotine dependence 40 .…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…Similar to smoking, current and lifetime nicotine dependence prevalences were higher among adults with past-year AUDs/ SUDs and lifetime AUDs than those without (Table 3). While this was generally consistent across studies, a study using data from adults who reported lifetime smoking and completed Wave 2 of the NESARC found that respondents with a past-year AUD were more likely to report past-year nicotine dependence while adults with lifetime AUD were less likely to report past-year nicotine dependence compared to those without AUDs 40 perhaps due to those with remitted AUDs being more likely to quit smoking (see Table 4). In that study, there were no significant gender differences in the relationships between AUDs/SUDs and past-year nicotine dependence 40 .…”
Section: Resultsmentioning
confidence: 52%
“…While this was generally consistent across studies, a study using data from adults who reported lifetime smoking and completed Wave 2 of the NESARC found that respondents with a past-year AUD were more likely to report past-year nicotine dependence while adults with lifetime AUD were less likely to report past-year nicotine dependence compared to those without AUDs 40 perhaps due to those with remitted AUDs being more likely to quit smoking (see Table 4). In that study, there were no significant gender differences in the relationships between AUDs/SUDs and past-year nicotine dependence 40 . Average level of nicotine dependence, as measured by the Fagerström Test for Nicotine Dependence 42 , was higher for German adults with current or remitted alcohol dependence compared to adults without alcohol use problems.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Despite their high prevalence and numerous associated adverse health consequences (Aharonovich et al, 2002; Blanco et al, 2014b; Degenhardt and Hall, 2012; García-Rodrígueza et al, 2014), many individuals with SUD do not receive treatment (Blanco et al, 2013a; Compton et al, 2007; Edlund et al, 2012; Hasin et al, 2007; Kessler et al, 1999; Olfson et al, 1998; Regier et al, 1993). The great extent of unmet need for substance abuse treatment underscores the critical public health importance of understanding factors that promote the flow of individuals with SUDs into treatment.…”
Section: Introductionmentioning
confidence: 99%